Pilot reuse sequences for TDD in downlink multi-cells to improve data rates - Adeeb Salh; Lukman Audah; Nor S. M. Shah; Shipun A. Hamzah (Universitas Ahmad Dahlan, 2019)
The exponential growth in demand for high data rate transmission to users in fifth generation wireless networks, focus there has been a particular research focus on new techniques that achievable high data rate by suppressing interference between neighboring cells. In this paper, we propose that system performance can be improved by using perfect channel estimation and reducing effective interference with pilot reuse that mitigate strong pilot contamination based on the knowledge of large-scale fading coefficients. We derived the lower bounds on the achievable data rate in downlink by analyzing the performance of the zero-forcing precoding method and derive the signal-to-interference noise ratio to mitigate interference between neighboring cells. From the simulation results, the large pilot reuse sequences improved the achievable data rate and provided better estimation for a channel. When the number of users is large, the interference between neighboring cells can be suppressed by using orthogonal pilot reuse sequences.